2021
DOI: 10.5937/jaes0-27851
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical research of the external temperature influence on the traction and speed properties and the fuel economy of cargo-carrying vehicles

Abstract: The manuscript proposes analytical methods for calculating fuel economy and traction-speed properties when modeling the movement of cargo-carrying vehicles on real routes, based on theoretical and experimental studies in a hot and dry climate, which allows for determining the efficiency of cargo-carrying vehicles objectively in terms of traction and speed, fuel and economic indicators. Using the statistical processing of experimental, theoretical research data, the authors calculate the coefficient X2, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The speed of traffic flows, traffic capacity, traffic safety and road ecology depend significantly on the technical level and operational condition of the road. With the increase of technical speed, the productivity of automobile transport increases with the constant amount of fixed costs, which reduces the cost of automobile transport per 1 t/km [13,14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The speed of traffic flows, traffic capacity, traffic safety and road ecology depend significantly on the technical level and operational condition of the road. With the increase of technical speed, the productivity of automobile transport increases with the constant amount of fixed costs, which reduces the cost of automobile transport per 1 t/km [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Objective assessment of the effectiveness of repair measures is related to the evaluation of a set of technical and economic indicators that reflect the required standards to ensure: speed and safety of traffic on the road, strength of the road surface and artificial structures, optimal transport costs, reasonable costs of road repair and maintenance [14,15].…”
Section: Methodsmentioning
confidence: 99%
“…where ρ1 and ρ2 are the density of the oil product at temperatures T1 and T2 The accuracy of determining β depends on the selected temperature range and the error in determining ρ1 and ρ2, which should be quite high, on the order of ±0.05-0.1% [5]. To process experimental data on the thermal conductivity of gas condensates using the method under consideration, experimental data on the density of gas condensates in Central Asia [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], which were measured according to the author's estimate with a maximum error of ±0.1%, were used. The proposed empirical equations for calculating λ of heavy petroleum products, obtained on the basis of the correlation between thermal conductivity and complexes and in the temperature range −20...150°С, give an error of no more than 8%.…”
Section: Recommended Methods For Calculating the Thermal Conductivity...mentioning
confidence: 99%
“…The application of formula (16) to calculate the thermal conductivity of the studied gas condensates showed that the rootmean-square error is ±1.0%, the maximum is 4.2%. Unlike equations ( 1), (13), the calculation of thermal conductivity using equation ( 16) does not require experimental values of λ, however, it is necessary to have data on the heat capacity (at 30°C) and the temperature dependence of density. As was shown above, the use of the law of corresponding states to calculate the thermal conductivity of gas condensates gives good results, but to use the resulting equations it is necessary to have at least one experimental value of the thermal conductivity of the gas condensate under study, which reduces their practical value.…”
Section: Recommended Methods For Calculating the Thermal Conductivity...mentioning
confidence: 99%
“…By 2020, according to a UN study, the world's transport sector accounts for almost a quarter of global energy-related greenhouse gas emissions. In particular, vehicle emissions, the main cause of urban air pollution, are a significant source of fine particulate matter (PM2.5) and nitrogen oxides (NOx) [5][6].…”
Section: Introductionmentioning
confidence: 99%